Isochromosome der(17)(q10)t(15;17) in acute promyelocytic leukemia resulting in an additional copy of the RARA-PML and loss of one p53 gene: Report of two cases and literature review - Đorđević Vesna; Denčić-Fekete Marija; Jovanović Jelica; Virijević Marijana; Kraguljac-Kurtović Nada; Jaković Ljubomir; Bogdanović Andrija (Vojnosanitetski Pregled)
Introduction. The isochromosome of the long arm of derivative chromosome 17, that originates from the translocation t(15;17) [ider(17)(q10)t(15;17), or ider(17q)] in acute promyelocytic leukemia (APL), is a rare chromosome aberration associated with a poor prognosis. Case report. We report the clinical and laboratory data associated with ider(17q) for two APL patients. Cytogenetic analysis of bone marrow cells in both cases showed a mosaic karyotype with the ider(17q); reverse transcription polymerase chain reaction (RT-PCR) was positive for the long (L) isoform of the retionic acid receptor alpha (PML-RARA) fusion transcript in each patient. Fluorescence in situ hybridization (FISH) analysis with the DNA probes for the PML gene on 15q24.1, and the RARA gene on 17q21.2, confirmed the extra copy of the RARA-PML fusion gene or ider(17q). Additionally, the FISH analysis with a DNA probe for the p53 gene on 17p13.1 confirmed loss of one copy of the universal tumor suppressor p53 in both patients. Conclusion. Both reported APL patients with ider(17q) had predominance of the clone with ider(17q) compared to those with t(15;17) and/or the normal karyotype, indicating that duplication of der(17) may provide a growth advantage allowing the relevant clone to become dominant. Moreover, as an important oncogenic event and poor prognostic factor in leukemia, loss of one gene copy of the tumor suppressor p53, may also contribute to this growth advantage. Although the clinical and prognostic significance for the patients with an ider(17q) remains unclear, cytogenetic and molecular-genetic analysis should be combined to reveal more details about this complex and rare chromosomal abnormality. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 41004]